Relationship between Caregiver Burden and Expressed Emotion in Families of Schizophrenic Patients - Nuralita, Nanda Sari; Camellia, Vita; Loebis, Bahagia (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Schizophrenia is a clinical syndrome that is variable, but highly disturbing; its psychopathology involves cognition, emotion, perception, and other aspects of behavior. Schizophrenic patients who are hospitalized, who return to a family environment characterized by high levels of criticism, excessive emotional involvement, or hostility (referred to as high expressed emotion), are more likely to experience the recurrence than schizophrenic patients returning to families characterized by low expressed emotion. AIM: We aimed to investigate relationship between caregiver burden and expressed emotion in families of schizophrenic patients. METHOD: This research is an analytic study with a cross-sectional approach. The research site is in the outpatient installation of BLUD Mental Health Hospital of North Sumatra Province using consecutive sampling non-probability sampling. The samples are family members who carry schizophrenic patients go to an outpatient installation at the BLUD Mental Health Hospital of North Sumatra Province that meets the inclusion and exclusion criteria. RESULT: The burden of care for the families of the most schizophrenic patients was mid load as many as 36 people, namely 36%, light burden of 34 people, 34%, no burden of 18 people, 18%, and heavy burden of 12 people, 12%. There is a significant relationship between the burden of treatment with expressed emotion, which is 0.004 (p < 0.05). CONCLUSION: In this study showed a significant relationship between the burden of treatment with expressed emotion (p = 0.004). This study is in accordance with the study conducted by Darwin in 2013, and Carra in 2012, which showed that there was a significant relationship between the burdens of treatment with expressed emotion in the families of schizophrenic patients. Other studies also show that the burden of care has an impact on emotional, physical health, social life, and financial status as a result of caring for sick people.